Educational Policy Of The Russian Federation Post-Soviet Period Regarding Learning Difficulties And Equity In Education - S.G. Kosaretsky (Moscow State University of Psychology and Education, 2023)
The article examines the educational policy of Russia of the post-Soviet period in relation to the problem of learning difficulties, disadvantaged students, equity in education. Changes in the relevance of tasks and the content of the proposed solutions are analyzed in legislation and strategic documents at different stages in the period from 1992 to 2022. The prospects of keeping the topic on the agenda of educational policy in the current conditions are discussed.